Prader-Willi Syndrome: Diagnostic Criteria - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 1993)
Diagnostic criteria for Prader-Willi syndrome (PWS), developed by consensus of seven clinicians in consultation with experts, are reported from the University of Washington, Seattle, and six additional centers.